Method for preparing iron phosphate dihydrate from hot furnace steel rolling slag and application of iron phosphate dihydrate

Through the steps of acid leaching, reduction, decomposition removal and oxidation, the hot furnace rolling slag is converted into battery-grade iron phosphate dihydrate, which solves the problem of resource utilization of hot furnace rolling slag, reduces the production cost of lithium iron phosphate batteries, and improves the performance stability of the battery.

CN119822343AActive Publication Date: 2025-04-15SICHUAN UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510252933.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-04-15
Estimated Expiration
2045-03-05

AI Technical Summary

Technical Problem

In the prior art, how to effectively utilize the hot furnace rolling slag generated by metallurgical enterprises as raw materials for lithium iron phosphate batteries, solves the problem of solid waste treatment and reduces production costs.

Method used

The hot furnace rolling slag is mixed with sulfuric acid and is subjected to acid leaching, and then the reduction reaction is carried out with iron powder, then the pH is adjusted by alkali liquid and decompression treatment is carried out, and finally mixed with ammonium dihydrogen phosphate under the action of an oxidizing agent to prepare iron phosphate dihydrate.

Benefits of technology

The resource utilization of hot furnace rolling slag was realized, and battery-grade iron phosphate dihydrate was prepared, which reduced the production cost of lithium iron phosphate batteries and improved the performance stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822343A_ABST
    Figure CN119822343A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing iron phosphate dihydrate from hot furnace steel rolling slag and application of the iron phosphate dihydrate, and belongs to the technical field of solid waste regeneration. The method comprises the following steps: by taking hot rolling furnace steel slag as a raw material, leaching an iron element under the action of sulfuric acid, reducing all the iron element into ferrous iron by using iron powder, adjusting the pH value by using ammonia water to remove impurities, oxidizing the ferrous iron into ferric iron under the action of an oxidizing agent, reacting with ammonium dihydrogen phosphate, and separating out iron phosphate precipitate to obtain iron phosphate intermediate slurry; and then carrying out solid-liquid separation, washing, aging, secondary solid-liquid separation, washing and drying to finally obtain the battery-grade iron phosphate dihydrate. The method provided by the invention realizes resource utilization of the hot rolling furnace steel slag, and is simple in process, convenient to operate and low in production cost; the product is high in purity, high in batch stability and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid waste regeneration, and in particular to a method for preparing ferric phosphate dihydrate by utilizing hot furnace-rolled steel slag and an application thereof. Background Art

[0002] Lithium iron phosphate batteries are widely used in passenger cars, buses, logistics vehicles, low-speed electric vehicles, etc. due to their good safety and low cost. At the same time, lithium iron phosphate batteries also have a series of unique advantages such as high operating voltage, high energy density, long cycle life, low self-discharge rate, no memory effect, green environmental protection, etc. They are suitable for large-scale electric energy storage and have good application prospects in the fields of safe grid connection of renewable energy power stations, grid peak regulation, distributed power stations, UPS power supplies, emergency power supply systems, etc.

[0003] At present, the preparation methods of lithium iron phosphate batteries are mainly divided into solid phase method and liquid phase method, among which high temperature solid phase reaction method is the most commonly used. Common solid phase methods include ferrous oxalate process route, iron phosphate process route, iron red process route, etc. Among them, the ferrous oxalate process route is the most mainstream production route, which has a simple process and is not easy to realize industrialization; however, it is very difficult to control the morphology of ferrous oxalate raw materials, resulting in poor processing performance of finished lithium iron phosphate. The lithium iron phosphate battery prepared by the iron phosphate process route has better performance stability; however, in the iron phosphate process route, iron phosphate accounts for more than 50% of the raw material cost, and the price per ton of product is high, which is not conducive to the development of the enterprise. To this end, the raw material cost of iron phosphate must be reduced so that the high-quality electrical performance of the battery prepared by the iron phosphate process route can match the market price.

[0004] Since most of the solid waste resources generated by metallurgical enterprises contain abundant Fe resources, the Fe resources are used for regeneration in the prior art. As a raw material for synthesizing lithium iron phosphate, it can not only solve the imminent solid waste treatment problem for steel enterprises, but also significantly reduce the production cost of lithium iron phosphate from the source, with obvious social and economic benefits. For example, in the patent application number CN202210835876.2, entitled "Method for preparing lithium iron phosphate as a positive electrode material for lithium batteries using iron-rich solid waste from the metallurgical industry", the iron-containing solid waste is regenerated to obtain ferrous oxalate, which is used as a raw material to produce lithium iron phosphate batteries using the ferrous oxalate process route.

[0005] In the above patent, among the solid waste resources to be recycled, Fe is Fe 3+ , Fe 2+The hot rolling process produces a large amount of byproducts, hot furnace rolling slag, which is mainly composed of Fe3O4 and contains a small amount of impurities such as Al, Co, Cr, Cu, Mn, Ni, Ti, Zn, and Mg. Therefore, combined with the raw material requirements for the preparation of lithium iron phosphate batteries, how to realize the resource utilization of hot furnace rolling slag is a technical problem that needs to be solved at present. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a method for preparing ferric phosphate dihydrate using hot furnace rolled steel slag and its application. The present invention uses hot furnace rolled steel slag and diammonium phosphate solution as raw materials to ultimately prepare battery-grade ferric phosphate dihydrate, thereby realizing the resource utilization of hot furnace rolled steel slag.

[0007] To achieve the above object, the present invention adopts the following technical solution: a method for preparing ferric phosphate dihydrate using hot furnace rolled steel slag, comprising the following steps:

[0008] (1) mixing hot rolling furnace slag with sulfuric acid solution, performing acid leaching treatment for a preset time, and then separating the solid and liquid to obtain an acid leaching solution;

[0009] (2) mixing the acid leaching solution of step (1) with a preset amount of iron powder, performing a reduction reaction, and then performing solid-liquid separation to obtain a reduced solution;

[0010] (3) adjusting the pH value of the reducing solution in step (2) with an alkali solution, performing a removal reaction, and then performing solid-liquid separation to obtain a ferrous solution;

[0011] (4) adjusting the pH of the ferrous solution in step (3) with an acidic solution, and then mixing the adjusted ferrous solution, ammonium dihydrogen phosphate and hydrogen peroxide to perform an oxidation reaction to obtain an intermediate ferric phosphate slurry;

[0012] (5) subjecting the intermediate ferric phosphate slurry in step (4) to solid-liquid separation, and washing the obtained solid material to obtain a crude ferric phosphate product;

[0013] (6) mixing the crude iron phosphate in step (5), water and phosphoric acid and aging the mixture to obtain an aged slurry;

[0014] (7) The aged slurry in step (6) is subjected to solid-liquid separation, and the obtained solid material is sequentially washed and dried to obtain battery-grade iron phosphate dihydrate.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] The present invention uses hot rolling furnace slag as raw material, and designs a set of methods that meet the regeneration and treatment of such solid waste according to the characteristics of the solid waste content in the hot rolling furnace slag, thereby ensuring that the regenerated ferric phosphate dihydrate can meet the battery-grade use standard.

[0017] The present invention firstly utilizes sulfuric acid to leach out the iron element, then utilizes a reducing agent to reduce all the iron element to divalent iron, and performs impurity removal treatment by adjusting the pH value of the system, then oxidizes the divalent iron to trivalent iron under the action of an oxidant, and adds ammonium dihydrogen phosphate to precipitate iron phosphate to obtain an intermediate slurry of iron phosphate; and then undergoes solid-liquid separation, washing, aging, solid-liquid separation again, washing again and drying to finally obtain battery-grade dihydrate iron phosphate.

[0018] The method provided by the present invention realizes the resource utilization of hot rolling furnace slag, and at the same time can obtain a dihydrate iron phosphate product with a stable structure and low price, so as to reduce the cost in the process of preparing lithium iron phosphate batteries using the iron phosphate process route, which is beneficial to the development of preparing lithium iron phosphate batteries using the iron phosphate process route and improves the performance stability of lithium iron phosphate batteries.

[0019] At the same time, the process of the invention is simple, easy to operate, and has low production cost; the product has high purity, strong batch stability, and is suitable for large-scale production.

[0020] Furthermore, in step (1): the mass of sulfuric acid is 120% in excess of the mass of hot rolling furnace slag;

[0021] The mass fraction of sulfuric acid solution is 50%;

[0022] The acid leaching treatment needs to be carried out with heat preservation and stirring, wherein the stirring speed is 400 rpm, the temperature is 90°C, and the stirring time is 120 min;

[0023] The pH value of the acid leaching solution is -0.20-0.00, and the mass content of the iron element is 2%-3.2%.

[0024] Furthermore, in step (2):

[0025] During the reduction reaction, the mixture was stirred under heat preservation, wherein the stirring speed was 200 rpm, the temperature was 20-40° C., and the time was 30 min;

[0026] The molar ratio of the iron element in the acid leaching solution to the iron element in the iron powder is 1:(0.2-0.3);

[0027] The pH of the reducing solution is 0.44-0.48.

[0028] Furthermore, in step (3):

[0029] During the impurity removal reaction, the mixture is stirred at a temperature of 200 rpm, a temperature of 20-40° C., and a time of 10-30 min.

[0030] The alkali solution includes ammonia water, the molar concentration of the ammonia water is 5-14 mol / L, and the ammonia water is used to adjust the pH of the reducing solution to 5.50.

[0031] Furthermore, in step (3):

[0032] The Al element content of the ferrous solution is less than 80ppm, the Co element content is less than 10ppm, the Cr element content is less than 10ppm, the Cu element content is less than 10ppm, the Mn element content is less than 80ppm, the Ni element content is less than 10ppm, the Ti element content is less than 80ppm, the Zn element content is less than 20ppm, and the Mg element content is less than 80ppm.

[0033] Furthermore, in step (4):

[0034] The oxidation reaction was carried out under heat preservation and stirring, wherein the stirring speed was 200 rpm, the temperature was 60° C., and the time was 10 min;

[0035] When the adjusted ferrous solution, ammonium dihydrogen phosphate and hydrogen peroxide are mixed:

[0036] Hydrogen peroxide and ammonium dihydrogen phosphate are added to the ferrous solution, the hydrogen peroxide is added for 50-60 minutes, the ammonium dihydrogen phosphate is added for 20-30 minutes, and the ammonium dihydrogen phosphate is added 50-60 minutes later than the hydrogen peroxide.

[0037] Furthermore, in step (4):

[0038] The acidic solution includes a dilute sulfuric acid solution, and the mass fraction of the dilute sulfuric acid solution is 5%-50%;

[0039] Using dilute sulfuric acid solution, adjust the pH of the ferrous solution to 2.00;

[0040] The molar ratio of the iron element in the adjusted ferrous solution to the phosphorus element in the diammonium phosphate is 1:(1.03-1.10), and the mass fraction of the diammonium phosphate is 13.83%;

[0041] The molar ratio of the hydrogen peroxide to the iron element in the adjusted ferrous solution is 1.5:1, and the mass fraction of the hydrogen peroxide is 10-15%.

[0042] Furthermore, in step (6):

[0043] The mass fraction of phosphoric acid is 85%, and the amount of phosphoric acid added is such that the molar ratio of iron element to phosphorus element in the system obtained by mixing the crude iron phosphate, water and phosphoric acid is 1:(1.00-1.15).

[0044] Furthermore, in step (7):

[0045] The drying temperature is 80-100° C., and the moisture content of battery-grade ferric phosphate dihydrate is ≤10wt%.

[0046] On the other hand, the application of the dihydrated iron phosphate of the present application is used in the production process of lithium iron phosphate batteries.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] The iron phosphate dihydrate prepared in this application has the same spectrum as the standard PDF card (77-0094), both of which have sharp diffraction peaks and obvious characteristic peaks, indicating that the material has a definite crystal structure and can be used as a raw material to prepare lithium iron phosphate batteries using the iron phosphate process route to obtain lithium iron phosphate batteries with better stability. In addition, since the iron phosphate dihydrate is prepared by solid waste regeneration, the raw material cost of iron phosphate is reduced to promote the matching of the high-quality electrical performance of the battery prepared by the iron phosphate process route with the market price, thereby obtaining a low-priced lithium iron phosphate battery with better stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is a SEM image of the battery-grade iron phosphate dihydrate prepared in Example 1 of the present invention;

[0050] Figure 2 This is the XRD pattern of battery-grade iron phosphate dihydrate prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0051] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0052] The main component of the hot rolling furnace slag of the present application is Fe3O4, and it also contains impurities such as about 590ppm Al, 50ppm Co, 320ppm Cr, 80ppm Cu, 3800pm Mn, 900ppm Ni, 180ppm Ti, 80ppm Zn, and 150ppm Mg.

[0053] Based on the composition characteristics of the hot rolling furnace slag, the present invention provides a method for preparing ferric phosphate dihydrate using hot rolling furnace slag, comprising the following steps:

[0054] (1) mixing hot rolling furnace slag with sulfuric acid, performing acid leaching, and then performing solid-liquid separation to obtain an acid leaching solution;

[0055] (2) mixing the acid leaching solution with iron powder, performing a reduction reaction, and then performing solid-liquid separation to obtain a reduced solution;

[0056] (3) adjusting the pH of the reducing solution with an alkali solution, performing a removal reaction, and then performing solid-liquid separation to obtain a ferrous solution;

[0057] (4) adjusting the pH of the ferrous solution with an acidic solution, and then mixing the adjusted ferrous solution, ammonium dihydrogen phosphate and hydrogen peroxide to perform an oxidation reaction to obtain a ferric phosphate slurry;

[0058] (5) subjecting the intermediate ferric phosphate slurry to solid-liquid separation, and washing the obtained solid material to obtain a crude ferric phosphate product;

[0059] (6) mixing the crude iron phosphate, water and phosphoric acid and aging the mixture to obtain an aged slurry;

[0060] (7) The aged slurry is subjected to solid-liquid separation, and the obtained solid material is sequentially washed and dried to obtain battery-grade ferric phosphate dihydrate.

[0061] According to the composition characteristics of hot rolling furnace slag, the present invention first mixes the hot rolling furnace slag with sulfuric acid, performs acid leaching treatment, and then separates the solid and liquid to obtain an acid leaching solution through the method in step (1). Specifically, the pH value of the acid leaching solution is preferably -0.20-0.00, and the content of iron in the acid leaching solution is preferably 2%-3.2%. In the present invention, the acid leaching process needs to be heat-insulated and stirred, the temperature is preferably 90°C, the stirring speed is preferably 400rpm, and the acid leaching time is preferably 120min. In the present invention, a mechanical stirrer is specifically used as a stirrer to provide stirring conditions. The solid-liquid separation method in the present invention specifically adopts vacuum filtration.

[0062] After obtaining the acid leaching solution, the present invention uses the method in step (2) to mix the acid leaching solution with iron powder, perform a reduction reaction, and then separate the solid and liquid to obtain a reduced solution. In the present invention, the molar ratio of the iron element in the acid leaching solution to the iron element in the iron powder is 1:(0.2-0.3).

[0063] In the present invention, the temperature of the reduction reaction is preferably 20-40°C, and the time of the reduction reaction is preferably 30 minutes. In the present invention, the reduction reaction is preferably carried out under stirring conditions, and the stirring speed is preferably 200 rpm; in the embodiment of the present invention, a mechanical stirrer is specifically used as a stirrer to provide stirring conditions. The solid-liquid separation method in the present invention specifically adopts vacuum filtration.

[0064] After obtaining the reduced solution, the present invention performs impurity removal treatment on the iron in the reduced solution by the method in step (3). To this end, the present invention first uses alkali solution to adjust the pH value, and the alkali solution is preferably ammonia water, and the molar concentration of ammonia water is 5-14 mol / L. The present invention uses ammonia water to adjust the pH value of the reduced solution, performs impurity removal reaction, and then separates the solid and liquid to obtain a ferrous solution.

[0065] In the present invention, the method of mixing the reducing liquid and the ammonia water includes: introducing the ammonia water into the reducing liquid by using a pump, and before the pH of the reducing liquid and the ammonia water system reaches 3.00, the molar concentration of the ammonia water is preferably 10-14 mol / L; after the pH of the reducing liquid and the ammonia water system reaches 3.00, the molar concentration of the ammonia water is preferably 5-10 mol / L.

[0066] In the present invention, the temperature of the impurity removal reaction is preferably 20-40°C; the time of the impurity removal reaction is preferably 10-30min; the time of the impurity removal reaction in the present invention specifically refers to the reaction time after the pH of the reducing liquid and ammonia water system reaches 5.50. In the present invention, the mixing of the reducing liquid and ammonia water and the impurity removal reaction are preferably carried out under stirring conditions, and the stirring speed is preferably 200rpm; in the embodiment of the present invention, a mechanical stirrer is specifically used as a stirrer to provide stirring conditions. The solid-liquid separation method in the present invention specifically adopts vacuum filtration.

[0067] After obtaining the ferrous solution, the present invention uses the method of step (4) to adjust the pH value of the ferrous solution with an acidic solution; specifically, the acidic solution is a dilute sulfuric acid solution, and the pH value of the ferrous solution is preferably adjusted to 2.00. In the present invention, the mass fraction of the dilute sulfuric acid is preferably 5%-50%.

[0068] In the present invention, the method of mixing the ferrous solution, ammonium dihydrogen phosphate and hydrogen peroxide comprises: adding hydrogen peroxide and ammonium dihydrogen phosphate to the ferrous solution, wherein the adding time of the hydrogen peroxide is preferably 50-60 minutes; the adding time of the ammonium dihydrogen phosphate is 20-30 minutes; the starting adding time of the ammonium dihydrogen phosphate is preferably 50-60 minutes later than the starting adding time of the hydrogen peroxide; specifically, the adding of the ammonium dihydrogen phosphate is started after the adding of the hydrogen peroxide is completed.

[0069] In the present invention, the temperature of the oxidation reaction is preferably 60°C; the time of the oxidation reaction is preferably 10 minutes; the time of the oxidation reaction in the present invention specifically refers to the reaction time after the addition of hydrogen peroxide and ammonium dihydrogen phosphate is completed. In the present invention, the addition of hydrogen peroxide and ammonium dihydrogen phosphate and the oxidation reaction are preferably carried out under stirring conditions, and the stirring speed is preferably 200rpm; in the embodiment of the present invention, a mechanical stirrer is specifically used as a stirrer to provide stirring conditions. In the present invention, the ferrous solution, ammonium dihydrogen phosphate and hydrogen peroxide precipitate iron phosphate to form an intermediate iron phosphate slurry.

[0070] After obtaining the intermediate ferric phosphate slurry, the present invention performs solid-liquid separation on the intermediate ferric phosphate slurry by the method in step (5), washes the obtained solid material, and obtains crude ferric phosphate. The solid-liquid separation method in the present invention specifically adopts vacuum filtration.

[0071] In the present invention, the washing is preferably re-pulping washing; the number of the re-pulping washing is preferably three times, which are recorded as one-stage re-pulping washing, one-stage re-pulping washing and one-stage re-pulping washing; specifically, the present invention performs vacuum filtration on the intermediate ferric phosphate slurry to obtain filter residue and one-stage mother liquor, and the water content of the filter residue is preferably ≤70%; the filter residue is subjected to one-stage re-pulping washing, and after the first vacuum filtration, a one-stage one-wash filter residue and a one-stage one-wash liquid are obtained, and the water content of the one-stage one-wash filter residue is preferably ≤70%; the one-stage one-wash filter residue is subjected to one-stage re-pulping washing, and after the second vacuum filtration, a one-stage two-wash filter residue and a one-stage two-wash liquid are obtained, and the water content of the one-stage two-wash filter residue is preferably ≤70%; the filter residue is subjected to one-stage re-pulping washing, and after the third vacuum filtration, a one-stage three-wash filter residue and a one-stage three-wash liquid are obtained, and the water content of the one-stage three-wash filter residue is preferably ≤70%, and the one-stage three-wash filter residue is the crude ferric phosphate.

[0072] In the present invention, the washing liquid used in the first repulping washing, the second repulping washing and the third repulping washing is preferably water, more preferably deionized water; the mass ratio of water (or deionized water) to the filter residue used in the first repulping washing, the second repulping washing and the third repulping washing is independently preferably (3.0-4.0):1.

[0073] After obtaining the crude iron phosphate, the present invention will use the method in step (6) to mix the crude iron phosphate, water and phosphoric acid and then age them to obtain an aged slurry.

[0074] In the present invention, the mass fraction of the phosphoric acid is preferably 85%, specifically, the phosphoric acid is industrial grade phosphoric acid with a mass fraction of 85%, and the water is preferably deionized water. In the present invention, the amount of phosphoric acid added is preferably such that the molar ratio of iron element to phosphorus element in the system obtained by mixing the crude iron phosphate, water and phosphoric acid is 1:(1.00-1.15).

[0075] In the present invention, the aging temperature is preferably 95°C; the time is preferably 4 hours; the aging is preferably carried out under stirring conditions, and the stirring speed is preferably 200 rpm. In the embodiment of the present invention, a mechanical stirrer is specifically used as the stirrer to provide stirring conditions.

[0076] After obtaining the aged slurry, the present invention will perform solid-liquid separation on the aged slurry through the method in step (6), and wash and dry the obtained solid material in sequence to obtain battery-grade ferric phosphate dihydrate.

[0077] The solid-liquid separation method described in the present invention specifically adopts vacuum filtration.

[0078] In the present invention, the washing is preferably re-pulping washing; the number of the re-pulping washing is preferably three times, which are recorded as two-stage re-pulping one washing, two-stage re-pulping two washings and two-stage re-pulping three washings in sequence; specifically, the present invention performs vacuum filtration on the intermediate ferric phosphate slurry to obtain filter residue and a first-stage mother liquor, and the water content of the filter residue is preferably ≤70%; the filter residue is subjected to two-stage re-pulping one washing, and after the first vacuum filtration, a two-stage one-wash filter residue and a two-stage one-wash liquid are obtained, and the water content of the two-stage one-wash filter residue is preferably ≤70%; the two-stage one-wash filter residue is subjected to two-stage re-pulping two washings, and after the second vacuum filtration, a two-stage two-wash filter residue and a two-stage two-wash liquid are obtained, and the water content of the two-stage two-wash filter residue is preferably ≤70%; the filter residue is subjected to two-stage re-pulping three washings, and after the third vacuum filtration, a two-stage three-wash filter residue and a two-stage three-wash liquid are obtained, and the water content of the two-stage three-wash filter residue is preferably ≤70%, and the two-stage three-wash filter residue is the crude ferric phosphate.

[0079] In the present invention, the washing liquid used in the second-stage repulping first washing, the second-stage repulping second washing and the second-stage repulping third washing is preferably water, and more preferably deionized water; the mass ratio of water (or deionized water) to the filter residue used in the second-stage repulping first washing, the second-stage repulping second washing and the second-stage repulping third washing is independently preferably (3.0-4.0):1.

[0080] In the present invention, the drying temperature is preferably 80-100° C.; the drying time is preferably based on the moisture content of the dried material being ≤10%, more preferably 2%-8%.

[0081] Example 1

[0082] A method for preparing ferric phosphate dihydrate using hot rolling furnace slag, the specific steps are as follows:

[0083] (1) 16 g of hot rolling furnace slag was added with 70.4 g of 50% sulfuric acid, and the mixture was acid-leached for 120 min at a stirring rate of 400 rpm and a temperature of 90° C., and then vacuum-filtered to obtain an acid leaching solution;

[0084] (2) The mass of the sulfuric acid is 120% in excess of the mass of the hot rolling furnace slag, the pH of the acid leaching solution is -0.06, and the content of iron in the acid leaching solution is 3%;

[0085] (3) mixing the acid leaching solution with 3.32 g of iron powder, performing an oxidation-reduction reaction for 30 min at a stirring rate of 200 rpm and a temperature of 40° C., and then vacuum filtering to obtain a reduced solution;

[0086] (4) pH of the reducing solution = 0.45;

[0087] (5) first adjusting the pH of the reducing solution to 3.30 with ammonia water having a molar concentration of 14 mol / L, and then adjusting the pH of the reducing solution to 5.50 with ammonia water having a molar concentration of 7 mol / L. After the pH of the reducing solution reaches 5.50, reacting for 30 min at a stirring rate of 200 rpm and a temperature of 40° C., and then vacuum filtering to obtain a ferrous solution;

[0088] (6) the pH of the ferrous solution is 5.35, the content of iron in the ferrous solution is 5.5%, the content of Al in the ferrous solution is 14.27 ppm, the content of Co is 1.53 ppm, the content of Cr is 6.64 ppm, the content of Cu is 2.27 ppm, the content of Mn is 63.23 ppm, the content of Ti is 4.43 ppm, the content of Zn is 12.30 ppm, and the content of Mg is 3.20 ppm;

[0089] (7) adjusting the pH of the ferrous solution to 2.00 with 5% by mass dilute sulfuric acid, preheating the obtained ferrous solution to 60° C. to obtain a preheated ferrous solution; adding 60 g of 11.82% by mass hydrogen peroxide to the preheated ferrous solution at a uniform speed, and the addition time of the hydrogen peroxide is 60 min; after the addition of the hydrogen peroxide is completed, adding 127.2 g of 13.83% by mass ammonium dihydrogen phosphate solution to the obtained system at a uniform speed, and the addition time of the ammonium dihydrogen phosphate solution continues for 31.8 min; after the addition of the hydrogen peroxide and the ammonium dihydrogen phosphate solution is completed, continuing the reaction at 200 rpm and 60° C. for 10 min to obtain an intermediate ferric phosphate slurry;

[0090] (8) The molar ratio of hydrogen peroxide to iron in the ferrous solution is 1.5:1; the molar ratio of iron in the ferrous solution to phosphorus in diammonium phosphate is 1:1.03;

[0091] (9) vacuum filtering the intermediate ferric phosphate slurry to obtain a mother liquor and a filter cake with a water content of 70%; using 200 g of deionized water as a washing liquid, the first-washed filter cake is subjected to a second-re-slurry washing, and after a second vacuum filtration, a second-washed liquid and a second-washed filter cake with a water content of 70% are obtained; using 200 g of deionized water as a washing liquid, the second-washed filter cake is subjected to a third-re-slurry washing, and after a third vacuum filtration, a third-washed liquid and a third-washed filter cake with a water content of 70% are obtained; the third-washed filter cake is the crude ferric phosphate;

[0092] (10) performing the first repulp washing, the second repulp washing and the third repulp washing using a mass ratio of deionized water to filter residue of 3.0:1;

[0093] (11) The crude iron phosphate was mixed with 180 g of deionized water and 1.92 g of 85% phosphoric acid by mass, and the mixture was manually stirred with a stirring paddle, and then aged at 200 rpm and 95° C. for 4 h to obtain an aged slurry;

[0094] (12) The molar ratio of iron in the crude iron phosphate to phosphorus in phosphoric acid is 1:0.12;

[0095] (13) Vacuum filtration is performed on the aged slurry to obtain a second-stage mother liquor and an aged filter cake with a water content of 70%; the aged filter cake is subjected to a second-stage re-slurry and a first wash using 200 g of deionized water as a washing liquid, and after the first vacuum filtration, a second-stage one-wash liquid and a second-stage one-wash filter cake with a water content of 70% are obtained; the second-stage one-wash filter cake is subjected to a second-stage re-slurry and a second wash liquid using 200 g of deionized water as a washing liquid, and after the second vacuum filtration, a second-stage two-wash liquid and a second-stage two-wash filter cake with a water content of 70% are obtained; the second-stage two-wash filter cake is subjected to a second-stage re-slurry and a third wash using 200 g of deionized water as a washing liquid, and after the third vacuum filtration, a second-stage three-wash liquid and a second-stage three-wash filter cake with a water content of 70% are obtained; the second-stage three-wash filter cake is dried at 80° C. for 8 h to obtain battery-grade ferric phosphate dihydrate.

[0096] After testing, the mass fraction of Fe element in the battery-grade iron phosphate dihydrate prepared in Example 1 is 29.09%, the mass fraction of P element is 16.62%, and the iron-phosphorus ratio is 0.971. The iron-phosphorus ratio in the iron phosphate dihydrate is controllable, so that the iron phosphate dihydrate can be used as a raw material in the production process of lithium iron phosphate batteries.

[0097] Example 2

[0098] A method for preparing ferric phosphate dihydrate using hot rolling furnace slag, the specific steps are as follows:

[0099] Preparation of battery grade iron phosphate dihydrate, the specific steps are as follows:

[0100] (1) 16 g of hot rolling furnace slag was added with 70.4 g of 50% sulfuric acid, and the mixture was acid-leached for 120 min at a stirring rate of 400 rpm and a temperature of 90° C., and then vacuum-filtered to obtain an acid leaching solution;

[0101] (2) the mass of the sulfuric acid is 120% in excess of the mass of the hot rolling furnace slag, the pH of the acid leaching solution is -0.07, and the content of iron in the acid leaching solution is 3.2%;

[0102] (3) mixing the acid leaching solution with 3.32 g of iron powder, performing an oxidation-reduction reaction for 30 min at a stirring rate of 200 rpm and a temperature of 40° C., and then vacuum filtering to obtain a reduced solution;

[0103] (4) pH of the reducing solution = 0.47;

[0104] (5) first adjusting the pH of the reducing solution to 3.30 with ammonia water having a molar concentration of 14 mol / L, and then adjusting the pH of the reducing solution to 5.50 with ammonia water having a molar concentration of 7 mol / L. After the pH of the reducing solution reaches 5.50, reacting for 30 min at a stirring rate of 200 rpm and a temperature of 40° C., and then vacuum filtering to obtain a ferrous solution;

[0105] (6) the pH of the ferrous solution is 5.39, the content of iron in the ferrous solution is 5.5%, the content of Al in the ferrous solution is 14.37 ppm, the content of Co is 0.89 ppm, the content of Cr is 7.58 ppm, the content of Cu is 3.31 ppm, the content of Mn is 53.48 ppm, the content of Ti is 3.28 ppm, the content of Zn is 14.58 ppm, and the content of Mg is 3.28 ppm;

[0106] (7) adjusting the pH of the ferrous solution to 2.00 with 5% by mass dilute sulfuric acid, preheating the obtained ferrous solution to 60° C. to obtain a preheated ferrous solution; adding 60 g of 11.82% by mass hydrogen peroxide to the preheated ferrous solution at a uniform speed, and the addition time of the hydrogen peroxide is 60 min; after the addition of the hydrogen peroxide is completed, adding 133.5 g of 13.83% by mass ammonium dihydrogen phosphate solution to the obtained system at a uniform speed, and the addition time of the ammonium dihydrogen phosphate solution continues for 33.4 min; after the addition of the hydrogen peroxide and the ammonium dihydrogen phosphate solution is completed, continuing the reaction at 200 rpm and 60° C. for 10 min to obtain an intermediate ferric phosphate slurry;

[0107] (8) The molar ratio of hydrogen peroxide to iron in the ferrous solution is 1.5:1; the molar ratio of iron in the ferrous solution to phosphorus in diammonium phosphate is 1:1.05;

[0108] (9) vacuum filtering the intermediate ferric phosphate slurry to obtain a mother liquor and a filter cake with a water content of 70%; using 200 g of deionized water as a washing liquid, the first-washed filter cake is subjected to a second-re-slurry washing, and after a second vacuum filtration, a second-washed liquid and a second-washed filter cake with a water content of 70% are obtained; using 200 g of deionized water as a washing liquid, the second-washed filter cake is subjected to a third-re-slurry washing, and after a third vacuum filtration, a third-washed liquid and a third-washed filter cake with a water content of 70% are obtained; the third-washed filter cake is the crude ferric phosphate;

[0109] (10) performing the first repulp washing, the second repulp washing and the third repulp washing using a mass ratio of deionized water to filter residue of 3.0:1;

[0110] (11) The crude iron phosphate was mixed with 180 g of deionized water and 2.01 g of 85% phosphoric acid by mass, and the mixture was manually stirred with a stirring paddle, and then aged at 200 rpm and 95° C. for 4 h to obtain an aged slurry;

[0111] (12) The molar ratio of iron in the crude iron phosphate to phosphorus in phosphoric acid is 1:0.12;

[0112] (13) Vacuum filtration is performed on the aged slurry to obtain a second-stage mother liquor and an aged filter cake with a water content of 70%; the aged filter cake is subjected to a second-stage re-slurry and a first wash using 200 g of deionized water as a washing liquid, and after the first vacuum filtration, a second-stage one-wash liquid and a second-stage one-wash filter cake with a water content of 70% are obtained; the second-stage one-wash filter cake is subjected to a second-stage re-slurry and a second wash liquid using 200 g of deionized water as a washing liquid, and after the second vacuum filtration, a second-stage two-wash liquid and a second-stage two-wash filter cake with a water content of 70% are obtained; the second-stage two-wash filter cake is subjected to a second-stage re-slurry and a third wash using 200 g of deionized water as a washing liquid, and after the third vacuum filtration, a second-stage three-wash liquid and a second-stage three-wash filter cake with a water content of 70% are obtained; the second-stage three-wash filter cake is dried at 80° C. for 8 h to obtain battery-grade ferric phosphate dihydrate.

[0113] According to the test, the mass fraction of Fe element in the battery-grade ferric phosphate dihydrate prepared in this embodiment is 28.55%, the mass fraction of P element is 16.42%, and the iron-phosphorus ratio is 0.964.

[0114] In order to further verify the performance of the dihydrated iron phosphate prepared in this application, this application takes the dihydrated iron phosphate prepared in Example 1 as an example for chromatogram analysis, and obtains Figure 1 , Figure 2 Results shown.

[0115] Figure 1 This is a SEM image of the battery-grade iron phosphate dihydrate prepared in Example 1. Figure 1 It can be seen that the battery-grade iron phosphate dihydrate particles prepared in Example 1 are evenly distributed, but there is a partial agglomeration phenomenon. Under a larger magnification field of view, it can be seen that many small particles of hundreds of nanometers are aggregated together to form agglomerates, the particle size distribution is uniform, and the surface is a large particle formed by the accumulation of flaky small particles, with a particle size of about 1-2 μm.

[0116] During the preparation of lithium iron phosphate batteries:

[0117] Evenly distributed particles of iron phosphate dihydrate can make the reaction more complete and more stable, which is conducive to the production of lithium iron phosphate materials with better structure and performance, thereby improving the battery's performance indicators such as charging and discharging efficiency, cycle life and safety, allowing the battery to maintain a good working condition in different environments and extend its service life.

[0118] Evenly distributed ferric phosphate dihydrate particles can avoid problems such as filtering and washing difficulties caused by particle agglomeration or uneven size, making solid-liquid separation, drying and other operations in the production process smoother, improving production efficiency, reducing production costs, shortening production cycles and increasing production capacity.

[0119] At the same time, the uniform particle distribution of ferric phosphate dihydrate can also ensure that the physical and chemical properties of each batch of products are similar, making the product quality more stable and uniform, meeting the strict requirements of product quality in different application fields, improving product reliability and consistency, and facilitating large-scale production and application.

[0120] Furthermore, in subsequent processing, such as mixing and molding with other materials, the evenly distributed particles of ferric phosphate dihydrate can be better mixed with other substances, thereby improving the fluidity and moldability of the mixture, making the processing smoother and obtaining a higher quality finished product.

[0121] Figure 2 The XRD pattern of the battery-grade iron phosphate dihydrate prepared in Example 1 is shown in FIG. Figure 2 It can be seen that the battery-grade iron phosphate dihydrate prepared in Example 1 has the same spectrum as the standard PDF card (77-0094), both of which have sharp diffraction peaks and obvious characteristic peaks, indicating that the material has a definite crystal structure, indicating that the iron phosphate dihydrate prepared in this application has stable chemical and physical properties, and meets the raw material requirements in the production process of lithium iron phosphate batteries.

[0122] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing ferric phosphate dihydrate using hot furnace rolled steel slag, characterized in that: The steps include: (1) mixing hot rolling furnace slag with sulfuric acid solution, performing acid leaching treatment for a preset time, and then separating the solid and liquid to obtain an acid leaching solution; (2) mixing the acid leaching solution of step (1) with a preset amount of iron powder, performing a reduction reaction, and then performing solid-liquid separation to obtain a reduced solution; (3) adjusting the pH value of the reducing solution in step (2) with an alkali solution, performing a removal reaction, and then performing solid-liquid separation to obtain a ferrous solution; (4) adjusting the pH of the ferrous solution in step (3) with an acidic solution, and then mixing the adjusted ferrous solution, ammonium dihydrogen phosphate and hydrogen peroxide to perform an oxidation reaction to obtain an intermediate ferric phosphate slurry; (5) subjecting the intermediate ferric phosphate slurry in step (4) to solid-liquid separation, and washing the obtained solid material to obtain a crude ferric phosphate product; (6) mixing the crude iron phosphate in step (5), water and phosphoric acid and aging the mixture to obtain an aged slurry; (7) The aged slurry in step (6) is subjected to solid-liquid separation, and the obtained solid material is sequentially washed and dried to obtain battery-grade iron phosphate dihydrate.

2. The method for preparing ferric phosphate dihydrate by using hot furnace rolled steel slag according to claim 1, characterized in that: In step (1), the mass of the sulfuric acid is 120% in excess of the mass of the hot rolling furnace slag; The mass fraction of sulfuric acid solution is 50%; The acid leaching treatment needs to be carried out with heat preservation and stirring, wherein the stirring speed is 400 rpm, the temperature is 90°C, and the stirring time is 120 min; The pH value of the acid leaching solution is -0.20-0.00, and the mass content of the iron element is 2%-3.2%.

3. The method for preparing ferric phosphate dihydrate by using hot furnace rolled steel slag according to claim 1, characterized in that: In step (2): During the reduction reaction, the mixture was stirred under heat preservation, wherein the stirring speed was 200 rpm, the temperature was 20-40° C., and the time was 30 min; The molar ratio of the iron element in the acid leaching solution to the iron element in the iron powder is 1:(0.2-0.3); The pH of the reducing solution is 0.44-0.

48.

4. The method for preparing ferric phosphate dihydrate by using hot furnace rolled steel slag according to claim 1, characterized in that: In step (3): During the impurity removal reaction, the mixture is stirred at a temperature of 200 rpm, a temperature of 20-40° C., and a time of 10-30 min. The alkali solution includes ammonia water, the molar concentration of the ammonia water is 5-14 mol / L, and the ammonia water is used to adjust the pH of the reducing solution to 5.

50.

5. The method for preparing ferric phosphate dihydrate by using hot furnace rolled steel slag according to claim 1, characterized in that: In step (3): The Al element content of the ferrous solution is less than 80ppm, the Co element content is less than 10ppm, the Cr element content is less than 10ppm, the Cu element content is less than 10ppm, the Mn element content is less than 80ppm, the Ni element content is less than 10ppm, the Ti element content is less than 80ppm, the Zn element content is less than 20ppm, and the Mg element content is less than 80ppm.

6. The method for preparing ferric phosphate dihydrate by using hot furnace rolled steel slag according to claim 1, characterized in that: In step (4): The oxidation reaction was carried out under heat preservation and stirring, wherein the stirring speed was 200 rpm, the temperature was 60° C., and the time was 10 min; When the adjusted ferrous solution, ammonium dihydrogen phosphate and hydrogen peroxide are mixed: Hydrogen peroxide and ammonium dihydrogen phosphate are added to the ferrous solution, the hydrogen peroxide is added for 50-60 minutes, the ammonium dihydrogen phosphate is added for 20-30 minutes, and the ammonium dihydrogen phosphate is added 50-60 minutes later than the hydrogen peroxide.

7. The method for preparing ferric phosphate dihydrate by using hot furnace rolled steel slag according to claim 6, characterized in that: In step (4): The acidic solution includes a dilute sulfuric acid solution, and the mass fraction of the dilute sulfuric acid solution is 5%-50%; Using dilute sulfuric acid solution, adjust the pH of the ferrous solution to 2.00; The molar ratio of the iron element in the adjusted ferrous solution to the phosphorus element in the diammonium phosphate is 1:(1.03-1.10), and the mass fraction of the diammonium phosphate is 13.83%; The molar ratio of the hydrogen peroxide to the iron element in the adjusted ferrous solution is 1.5:1, and the mass fraction of the hydrogen peroxide is 10-15%.

8. The method for preparing ferric phosphate dihydrate by using hot furnace rolled steel slag according to claim 1, characterized in that: In step (6): The mass fraction of phosphoric acid is 85%, and the amount of phosphoric acid added is such that the molar ratio of iron element to phosphorus element in the system obtained after the crude iron phosphate, water and phosphoric acid are mixed is 1:(1.00-1.15).

9. The method for preparing ferric phosphate dihydrate by using hot furnace rolled steel slag according to claim 1, characterized in that: In step (7): The drying temperature is 80-100° C., and the moisture content of battery-grade ferric phosphate dihydrate is ≤10wt%.

10. Application of battery-grade iron phosphate dihydrate in the production process of lithium iron phosphate batteries.

Citation Information

Patent Citations

  • Method for preparing lithium iron phosphate, a cathode material for lithium batteries, from iron-rich solid waste in the metallurgical industry.

    CN115463935B

  • Preparation method of precursor iron phosphate of cathode material lithium iron phosphate of lithium ion battery

    CN101640268A

  • Lithium iron phosphate composite material, its preparation method and application

    CN102437311A

  • Lithium iron phosphate battery pigment composite board prepared from red mud

    CN109987638A

  • Iron oxyhydroxide desulfurization catalyst prepared from titanium dioxide by-product copperas and preparation method thereof

    CN114768837A